Exploring conditional indirect effects: a structural equation modeling approach - Sandoval Álvarez, Carlos Alberto (2025)
Empirical testing of conditional indirect effect models is often considered challenging for researchers. Frequently, there is a lack of clarity regarding the appropriate setup and analysis. The objective of this tutorial is to contribute to the methodological literature in the field of management by proposing a simple but powerful approach to test conditional indirect effects. Proposal: it is twofold: first, it aims to elucidate the conceptual underpinnings that are essential for discerning the distinctions between mediation, moderation, and moderated mediation; second, it aims to provide the reader with a demonstrative example that outlines the step-by- step methodology for accurately parameterizing research models to test conditional indirect effects using the robust technique of covariance-based structural equation modeling. This methodological approach is designed to reveal the intricate mechanisms underlying cause-effect relationships within these complex models. The tutorial also delineates the treatment and interpretation of the data. Conclusions: the main contribution of this tutorial is to provide an easy-to-understand methodology on a complex topic such as conducting conditional indirect effect studies, thus allowing for substantial improvements in the quality of research in the field of management studies.